UKRAINIAN-LANGUAGE PERIODICS OF THE US DIASPORA AS AN IMPORTANT FACTOR OF MAINTAINING COMMUNICATION BETWEEN EMIGRATION AND UKRAINE - BILOVUS, Lesia; YABLONSKA, Natalia (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2022)
The purpose of the study is to analyse and to make thetypology of Ukrainian-language periodicals of the US diaspora, and their impact on the preservation of national identity. The research methodology is based on the principles of historicism, systematicity, scientificity, verification, authorial objectivity, as well as the use of general scientific and special historical methods. The scientific novelty is that the typology of such periodicals is made on basis of the regularity of publication, the relevance of content, diversity, consistency of the title, the direction of the publication, the presence of an organization (one or more) or media group, the body of which is this publication, also individual journals of different directionsare analysed. Conclusions. Preservation of one's own culture, native language, and faith in the international environment is possible, and periodicals play an important role in it. Ukrainian-language newspapers and magazines in the US diaspora have helped keep immigrants in touch with their homeland, becoming an element that unites them around their national identity. Analysis of newspapers and individual magazines of the Ukrainian People's Union, the Union of Ukrainian Women of America, church and art shows that they have become an important element of our ethnic life in the United States and helped preserve their language, culture, and faith and national worldview.